Kontrowersyjna twórczość: opracowanie, kontynuacja, rekonstrukcja - Stępień, Małgorzata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The conclusion of the considerations in this paper is that the analysis, reconstruction and continuation of a given work of art will probably always raise some doubts since they concern the existing work, and any kind of intervention infringes on this work’s right to remain integral. Therefore the original work of art should always come first whereas an analyst, translator, continuator and reconstructor should stay respectfully in the background.